Biogeochemical coupling of C/Fe in oil-polluted wetlands associated with iron reduction - Xiaolin Zhang; Wendan Xue; Guoliang Wang; Jieliang Liang; Qi Wang; Yuhao Li; Wensheng Shu; Qixing Zhou (Communications Earth & Environment)
Abstract Oil contamination in coastal wetlands jeopardizes these ecosystems and worsens climate warming. Here we analyze 87 metagenomic samples from representative Chinese wetland oilfields and find that genes associated with dissimilatory iron reduction respond to hydrocarbon levels. These genes were closely linked to the breakdown of organic matter into carbon dioxide and methane, highlighting the potential of dissimilatory iron reduction for degrading stubborn hydrocarbons and altering electron transfer pathways. Notably, Geobacter, a key genus for dissimilatory iron reduction, showed strong correlation with iron(II) production and hydrocarbon degradation. To validate these findings, a targeted enhancement of dissimilatory iron reduction with external iron oxide and Geobacter maximized carbon removal, transforming organic-bound fraction of iron into carbonate-bound fraction. The intensified iron reduction process reduced methane emissions by 38–40% and strengthened microbial interactions by redirecting electron transfer in carbon flow. Our study innovatively mitigates pollution and reduces methane emissions in oil-contaminated wetlands.